Stress in the Preschool Profession: Action Research - Jukić, Tonća; Tomić Kaselj, Iskra (Revija za elementarno izobraževanje, 2024)
Stress has become an integral part of modern humans’ busy lives. One of the professions in which stress is highly prevalent is that of a preschool teacher. Therefore, action research was conducted in a higher education context aimed at reducing preschool teacher stress. After one month of introducing changes that met teachers’ interests and needs and realizing their baseline values, teacher stress was reduced. Moreover, the research produced multiple benefits on both the personal and professional levels. The paper points to the need to organize a motivating pedagogical environment in higher education, which will make positive changes in students’ lives and in their professional development.
Keywords: experiential teaching, occupational stress, preschool teachers, values, well-being.